A reagentless electrochemical immunosensor based on probe immobilization and the layer-by-layer assembly technique for sensitive detection of tumor markers. Issue 22 (29th October 2015) - Qiumei, Cong; Hongmei, Bian; Zhaoxia, Yu; Liu, Jiyang; Xi, Fengna
Abstract : Combined with surface-confined probes and the layer-by-layer assembly technique, a reagentless electrochemical immunosensor was constructed for highly sensitive detection of carcinoembryonic antigen. Abstract : Facile electrochemical methods for highly sensitive detection of tumor markers provide great advances in early clinical diagnosis of cancer and public health protection. Herein, a reagentless electrochemical immunosensing platform was developed for sensitive immunoassay of tumor biomarkers based on surface-confined probes and the layer-by-layer assembly technique. Ferrocene grafted cationic polymer polyethyleneimine (PEI–Fc) was modified on chemically reduced graphene oxide (rGO) to form a redox-active and positively charged PEI–Fc–G nanocomposite. Through the layer-by-layer electrostatic assembly technique, the positively charged PEI–Fc–G and negatively charged anionic polyelectrolyte sodium-p-styrene (PSS) were alternately assembled on a negatively charged Au electrode. Based on the biospecific binding of lectin and sugarprotein, the concanavalin A (Con A) lectin monolayer served as the linker to immobilize sugarprotein (horseradish peroxidase, HRP) labeled anti-CEA antibody (HRP-Ab) on the surface of the (PEI–Fc–G/PSS) n /PEI multilayer substrate. With carcinoembryonic antigen (CEA) being the model tumor biomarker, the as-prepared immunosensor presented high selectivity and good stability for sensitive and reagentless detection of CEA with a wide range of 0.1 ng mL −1 to 120 ng mL −1 ( R 2 = 0.9963) and a detection limit as low as 60 pg mL −1 at a signal/noise ratio of 3. The proposed immunosensor might serve as a versatile platform for reliable cancer diagnostics clinical and biochemical analysis.